Exosomal-mediated transfer of OIP5-AS1 enhanced cell chemoresistance to trastuzumab in breast cancer via up-regulating HMGB3 by sponging miR-381-3p - Yu Qiang (De Gruyter, 2021)
Long noncoding RNA OPA-interacting protein 5 antisense transcript 1 (OIP5-AS1) was confirmed to involve in the malignancy of breast cancer. However, whether exosomal OIP5-AS1 is implicated in trastuzumab resistance remains unclear.